REBRANDING LOGO FESTIVAL PESONA WISATA KERINCI - Rino Yuda Rino Yuda Rino Yuda; Andar Indra Sastra; Syafwandi Syafwandi (Ranah Seni, 2018)
ABSTRACT Kerinci Regency has many natural attractions, arts and cultural diversity and has become the center of natural tourist attractions, Arts and Culture, In line with the main objective of the Kerinci Regency Government, an event called Kerinci Festival was then organized. Therefore, it is necessary to redesign the brand to make it more attractive, consistent, and effective. The establishment of a Brand image can be done by designing the logo in advance and supported by the activity attributes (supporting media) of the festival which has a unified entirety to be easily remembered. Data collection method was used in this design through observation, interview, literature, documentation, and data analysis using SWOT and AISAS analyses. The next process was carried out by creating a new brand with the main media in the form of Kerinci festival logo of tourism enhancement, and supporting media such as festival attributes, print publications and audiovisual media that consistently have unity in Branding. The logo of the "Kerinci Tourism Charm Festival" consists of a visual form of the Asyiek dance and a combination of the Klouk Pakou motif supported by the tagline or slogan of Nature, Arts and Culture as the brand image of the Festival of Kerinci Tourism enhancement. 297